Effect of nickel induced respiratory alterations in fresh water bivalve, lammellidens marginalis - Andhale, A V; Zambare, S P (International Multidisciplinary Research Journal, 2012)
The rate of oxygen consumption was measured in nickel chloride treated bivalve for 15 and 30 days and compared to the levels of controlled bivalves. The study shows that the average oxygen consumption rate was decreased in treated as compared to controlled bivalves.